Biskuit daun kelor (Moringa oleifera) berpengaruh terhadap kadar hemoglobin pada remaja putri yang anemia - Nur Khofifah; Mardiana Mardiana (AcTion: Aceh Nutrition Journal, 2023)
Moringa leaves (Moringa oleifera) are a plant that contains many multi-nutrients, especially Fe, folate, Ca, and phosphorus. Moringa leaves contain iron which is an essential element for forming hemoglobin. This study aims to determine the effect of giving Moringa leaf biscuits on the hemoglobin levels of anemic adolescent girls. This research is quantitative field research. This research was conducted at the Hufadzul Qur'an Al Asror Islamic Boarding School in Semarang in 2021 with a sample of 37 anemic adolescent girls. The sample used the total sampling method. Data were collected through interviews and 24-hour recall. Hb level examination through the Sahli method and BMI measurement based on weight and height. Statistical analysis was Paired sample t-test and Linear Regression test. The results showed that the average hemoglobin level of adolescent girls before the intervention was 10,8 g/dl, and the average hemoglobin level after the intervention was 12,9 g/dl. After the intervention, 33 respondents did not experience anemia, and four still had anemia. The respondents' average energy, protein, and iron intake was sufficient, with an energy intake of 2139 kcal/day, protein 63,1 g/day, and iron 23,1 mg/day. Statistical results showed a significant increase in hemoglobin levels before and after the intervention (p= 0,001). The conclusion is that giving Moringa leaf biscuits has an effect on the enhancement of hemoglobin levels of anemic adolescent girls.